Lecturer dress code and student perceptions of lecturer professional attributes. Issue 2 (4th March 2019) - Slabbert, Anke
Abstract : This study explored how students' perceptions of their lecturers' dress code influenced their inferences about the professional competences of the lecturers. Survey respondents were 102 students from a South African university of technology (female = 60%; age range = 18 to 25 years, SD: Image 1 = 0.75; Image 2 = 0.60; Image 3 = 0.83 and Image 4 = 0.67). They responded to a structured survey with picture illustration figures of alternative dress code and across dimensions of professional competences: rapport, fairness, knowledge and credibility, and organisation and preparation. The findings suggest that lecturers' dress code does influence students perceptions of lecturers' qualities in the academic work environment. Results showed that students percieve both male and female professionally dressed lecturers more positively than casually dressed lecturers. Furthermore, instructor attire did not affect female and male students differently.